Mortality in Thai Nursing Homes Based on Antimicrobial-Resistant Enterobacterales Carriage and COVID-19 Lockdown Timing: A Prospective Cohort Study - Thundon Ngamprasertchai; Muthita Vanaporn; Sant Muangnoicharoen; Wirichada Pan-ngum; Narisa Ruenroengbun; Pittaya Piroonamornpun; Thitiya Ponam; Chatnapa Duangdee; Phanita Chankete; Anupop Jitmuang; Visanu Thamlikitkul (Antibiotics, 2022)
Antimicrobial-resistant Enterobacterales carriage and the coronavirus disease 2019 (COVID-19) lockdown measures may impact the incidence all-cause mortality rate among nursing home residents. To determine the all-cause mortality rate in the presence/absence of antimicrobial-resistant Enterobacterales carriage and the incidence all-cause mortality rate before and during COVID-19 pandemic lockdown, this prospective closed-cohort study was conducted at various types of nursing homes in Bangkok, Thailand, from June 2020 to December 2021. The elderly residents included 142 participants (aged ≥60 years) living in nursing homes ≥3 months, who did not have terminal illnesses. Time-to-event analyses with Cox proportional hazards models and stratified log-rank tests were used. The all-cause mortality rate was 18%, and the incidence all-cause mortality rate was 0.59/1000 person-days in residents who had antimicrobial-resistant Enterobacterales carriage at baseline. Meanwhile, the incidence all-cause mortality rate among noncarriage was 0.17/1000 person-days. The mortality incidence rate of carriage was three times higher than residents who were noncarriage without statistical significance (HR 3.2; 95% CI 0.74, 13.83). Residents in nonprofit nursing homes had a higher mortality rate than those in for-profit nursing homes (OR 9.24; 95% CI 2.14, 39.86). The incidence mortality rate during and before lockdown were 0.62 and 0.30, respectively. Effective infection-control policies akin to hospital-based systems should be endorsed in all types of nursing homes. To limit the interruption of long-term chronic care, COVID-19 prevention should be individualized to nursing homes.